Need for the Government Control over Religious and Charitable Endowments: The Nexus between Government Control and Cultural Heritage (Journal of Advances and Scholarly Researches in Allied Education, 2022)
When we talk about a religious endowment, we mean all the assets that belong to or have been bestowed in support of a Hindu religious organisation, or that have been endowed to conduct public service or charitable work associated with the institution or another religious charity. As a statutory entity, the Hindu Religious and Charitable Endowments Board has a President and two to four Commissioners who are appointed by the government. Muslims and Christians are not funded by the Indian government, although temples and other religious organisations are. It's either that, or the government has to subsidise all of them or none of them and keep it private. Religious institutions must be liberated from the grip of the state since a temple is first and foremost a subjective matter. A temple can't function properly with just a few of staff. You'll need a lot of zeal and commitment to pull this out. However, temples are currently under the jurisdiction of the government, and someone who lacks a personal connection to the temple is in charge of maintaining it. A temple is more than a place of worship it is the lifeblood of a community. It can only be managed with tremendous involvement and devotion.”